Caring for prisoners: towards mindful practice. (March 2013) - Walsh, Elizabeth; Freshwater, Dawn; Fisher, Pamela
Those caring for prisoners are subject to the influences of the dominant custodial discourses of security and risk management that prevail in a prison environment. The conflicting caring and custodial roles adopted by nurses working in prisons and by prison officers constitute the foundation for further exploration of prisoner care in the wider healthcare literature. In this discussion paper, we argue that the identities and practices of those working in prison care are significantly shaped by organisational and societal discourses and that these generate rigidities and defensive mechanisms that limit the development of practice. We argue that a greater emphasis on mindfulness in professional development and clinical supervision may be helpful in enabling prison workers involved in caring roles to enter a professional dialogue characterised by openness, inclusion and engagement. This, we argue, would facilitate the development of newer and richer understandings of practice and to a revitalisation of professional engagement.